Teaching Human Rights in Commonwealth University Law Schools: Approaches and Challenges, With Passing References to Some South African Experiences - John Cantius Mubangizi; DJ McQuoid-Mason (Obiter, 2020)
There have been a number of international commitments by members of the United Nations, including Commonwealth countries, to include human-rights education in their formal and informal education programmes. In addition, the Commonwealth Legal Education Association (CLEA), under the auspices of the Commonwealth Secretariat, has produced a Model Human Rights Curriculum for Commonwealth countries. Despite these initiatives, there appears to have been no systematic programme for introducing human-rights education at Commonwealth universities. An increasing number of Commonwealth law schools, however, have introduced human-rights law by integrating it into existing law courses as a “stand-alone” optional or core course, or as a combination of both. In addition, university-based centres for human rights have been established. The importance of the role that universities can play in advancing human rights in countries transitioning from autocracy to democracy is illustrated with passing references to the South African experience.